34. DEVELOPMENT OF A SELF-ASSESSMENT QUESTIONNAIRE FOR EVALUATING PROFESSIONAL CARE PRACTICE COMPETENCY IN PEDIATRIC NURSING (Vietnam Journal of Community Medicine, 2025)
Objective: To develop and validate a self-assessment questionnaire for evaluating professional care competency in pediatric nursing using the Delphi method.Methods: The study was conducted in two phases. Phase 1 the initial draft of the questionnaire was developed based on the 2022 Vietnamese Nursing Competency Standards, international competency frameworks, and existing pediatric nursing assessment tools. Phase 2 the questionnaire was validated through four rounds of the Delphi method involving 10 experts. Items were assessed based on 4 attributes: relevance, clarity, comprehensiveness, and appropriateness. The I-CVI, S-CVI/Ave, and S-CVI/UA indices were calculated, and expert group discussions were conducted to determine the level of consensus.Results: The finalized questionnaire consists of 3 domains, 12 standards, and 79 items. All items achieved perfect scores of 1.0 for I-CVI, S-CVI/Ave, and S-CVI/UA, indicating a high level of validity and expert agreement. Group discussions also confirmed strong consensus regarding the structure, content, and rating scale of the questionnaire.Conclusion: The questionnaire demonstrates strong validity in both structure and format, making it suitable for further application in assessing and developing pediatric nursing competencies in Vietnam
Keywords: Competency; nursing; pediatric; questionnaire; Delphi method.